The relationship between family support and improved nutritional status in Tuberculosis (TB) patients - Ambia Nurdin; Ferdi Riansyah; Ristiani Ristiani; Syariena Syariena; Gadis Halizasia (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
Tuberculosis (TB) is an infectious disease that substantially affects the nutritional status of patients. Family support is believed to contribute to improved nutritional outcomes during the treatment. This study aimed to determine the relationship between family support and improvements in the nutritional status among TB patients with TB. A quantitative study with a cross-sectional design was conducted between May and June 2024, involving 44 patients with TB at the Langkahan Primary Health Center, North Aceh. Data were collected using a validated questionnaire that assessed four dimensions of family support and nutritional status. The Chi-square test was used for data analysis (p < 0.05). A total of 75% of the patients demonstrated improvements in their nutritional status. Overall family support was significantly associated with improved nutritional status (p = 0.013; OR = 7.875; 95% CI: 1.733–35.785), and all support dimensions showed significant relationships (p < 0.05). These findings indicate that family support plays an essential role in enhancing the nutritional status of patients with TB. Strengthening family based interventions is recommended to support nutritional recovery and successful treatment.